Photosynthetic plasticity of the genus Asparagopsis (Bonnemaisoniales, Rhodophyta) in response to temperature: implications for invasiveness - Zanolla-Balbuena, Maríanela Fernanda; Altamirano-Jeschke, María; Carmona-Fernández, Raquel; De la Rosa, Julio; Sherwood, Alison; Andreakis, Nikos (Springer, 2014)
Invasive species display remarkable levels of ecophysiological plasticity, which supports colonization, population establishment and fitness across their introduction range. The red seaweed genus Asparagopsis comprises genetically homogeneous invasive species (A. armata) and cryptic species complexes (A. taxiformis sensu lato) consisting of invasive mitochondrial lineages introduced worldwide. The photosynthetic plasticity of Australian, Mediterranean and Hawaiian Falkenbergia stages (i.e. the tetrasporophytic stage) of A. taxiformis lineages 2, 3 and 4 and Mediterranean isolates of A. armata was assessed by challenging their photosynthetic performance at five different temperatures (12–26 C). Our aim is to portray the photosynthetic profiles in relation to temperature for each of the aforementioned Asparagopsis OTUs. We additionally test the physiological response of A. taxiformislineage 2 sampled within its invasive (Mediterranean Sea) and native range (Australia) to identify physiological features associated with invasive strains. Based on photosynthesis optima, Asparagopsis isolates were recovered into a tropical (NL2 and L4) and a temperate (AA, Il2 and L3) group that presented no differences in most photosynthetic parameters at the experimental temperatures, thus indicating a greater physiological plasticity. On the other hand, low Ic values together with an apparent lack of sensitivity in the photosynthetic response to changing temperatures were revealed for the Mediterranean lineage 2, indicative of adaptive benefits that likely support its invasive success compared to the rest of the genus. Our results represent a valuable resource to predict distributional shifts in some of the lineages and to anticipate control programs for lineage 3, potentially invasive
Keywords: Fotosíntesis; Plantas acuáticas; Asparagopsis; Climate Change; Invasive; Plasticity; Photosynthesis; Temperature